2021
DOI: 10.1002/jcp.30367
|View full text |Cite
|
Sign up to set email alerts
|

Higher infectivity of the SARS‐CoV‐2 new variants is associated with K417N/T, E484K, and N501Y mutants: An insight from structural data

Abstract: The evolution of the SARS‐CoV‐2 new variants reported to be 70% more contagious than the earlier one is now spreading fast worldwide. There is an instant need to discover how the new variants interact with the host receptor (ACE2). Among the reported mutations in the Spike glycoprotein of the new variants, three are specific to the receptor‐binding domain (RBD) and required insightful scrutiny for new therapeutic options. These structural evolutions in the RBD domain may impart a critical role to the unique pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
427
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 321 publications
(476 citation statements)
references
References 51 publications
45
427
3
1
Order By: Relevance
“…In this regard, in silico techniques such as MD simulations were utilized to study the said mutations role in PZase resistance to PZA. These methods are widely used to understand the mechanism of resistance and any binding perturbation caused by mutations ( Khan et al, 2020c , e , 2021a , b ). It unveils conformational changes of proteins caused by any intrinsic mutations or ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in silico techniques such as MD simulations were utilized to study the said mutations role in PZase resistance to PZA. These methods are widely used to understand the mechanism of resistance and any binding perturbation caused by mutations ( Khan et al, 2020c , e , 2021a , b ). It unveils conformational changes of proteins caused by any intrinsic mutations or ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant vaccines comprising the Spike RBD induced potent antibody response in immunized animal models such as mouse, rabbits and primates [13]. On the other hand, mutations in the RBD can improve viral affinity to ACE2 and the evasion from neutralization antibodies [8,[14][15][16]. A recently published clinical study [17] has shown also a decreased vaccine efficacy against the lineage B.1.351 (carrying Spike mutations E484K and N501Y), testifying the need to track and monitor all SARS-CoV-2 mutations, with a particular accent on those affecting the Spike RBD.…”
Section: Introductionmentioning
confidence: 99%
“…This explains to a certain extent the phenomenon that the well-known N501 mutation will lead to stronger affinity. 44 …”
Section: Resultsmentioning
confidence: 99%